Identification of key genes associated with muscle atrophy after spinal cord injury and experimental verification in rats - Wang, Xiang; Gao, Yimin; Huo, Jianzhong (Frontiers in Immunology, 2026)
BackgroundSpinal cord injury (SCI) is a neurological disease with high morbidity and mortality. Post-SCI muscle atrophy is a cascade response to SCI, and failure to actively prevent its occurrence severely affects patients’ mobility and quality of life. Therefore, deeply exploring the correlation between muscle atrophy after SCI and the molecular regulation mechanism is of great significance.MethodsDownload GSE21497 expression profile data from the gene expression omnibus (GEO) database. Perform weighted gene co-expression network analysis (WGCNA) on the obtained differentially expressed genes (DEGs). Subsequently, we performed functional and pathway enrichment analyses of key modules. Construct a protein-protein interaction (PPI) network and screen core genes. Finally, the results were verified by real-time polymerase chain reaction(PCR).ResultsA total of 1007 DEGs were obtained, including 533 upregulated genes and 474 downregulated genes. WGCNA analysis identified 161 turquoise modules of DEGs as key modules related to SCI. Functional enrichment analysis showed that these genes were mainly enriched in negative regulation of cellular process, cytosol, response to organic substance, endpoint system, extracellar region, peroxisome proliferators-activated receptors (PPARs) signaling, adherens junction signaling, and DNA replication signaling pathway.ConclusionsFOS and CCL2 may be involved in the molecular pathophysiology of muscle atrophy after SCI, serving as potential targets for diagnosis or treatment of SCI-related muscle atrophy.